Country Programs for Impact: WorldFish in Zambia - Siamudaala, Victor; Mudege, Netsayi; Fleming, Ann; Majumdar, Rajita (WorldFish, 2025)
Over the past 5 years, WorldFish’s work in Zambia has delivered tangible, measurable change, especially for smallholder farmers, women and youths in rural communities. In the remote provinces of Northern and Luapula, where access to quality fish seed, feed and training is limited, WorldFish introduced practical, inclusive models that have strengthened livelihoods and reshaped local food systems.